2012
DOI: 10.1161/circoutcomes.111.962621
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of an Underperforming Implantable Cardiovascular Device Using an Automated Safety Surveillance Tool

Abstract: Background— Postmarket medical device surveillance in the United States depends largely on voluntary reporting of adverse events. Consequently, early safety signals may be missed, exposing patients to potentially hazardous products. The aim of this study was to assess the feasibility of using an automated safety surveillance tool to detect early signals that a marketed implantable cardiac device was underperforming. Methods and Results— For this purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In addition, modeling failure rates derived from our observational findings indicated that traditional approaches to ICD lead surveillance—even if bolstered by unique device identifiers—will need robust sample sizes with long follow-up to demonstrate meaningful deviations in performance within the normal range. However, our simulation results also support efforts to identify seriously flawed leads, such as Sprint Fidelis, in near real time using multicenter implant and follow-up databases 17. In sum, these data should buttress confidence in current standards for transvenous lead design, while also providing essential clinical and statistical context for ongoing discussions regarding postmarket surveillance and comparative effectiveness research in this area.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, modeling failure rates derived from our observational findings indicated that traditional approaches to ICD lead surveillance—even if bolstered by unique device identifiers—will need robust sample sizes with long follow-up to demonstrate meaningful deviations in performance within the normal range. However, our simulation results also support efforts to identify seriously flawed leads, such as Sprint Fidelis, in near real time using multicenter implant and follow-up databases 17. In sum, these data should buttress confidence in current standards for transvenous lead design, while also providing essential clinical and statistical context for ongoing discussions regarding postmarket surveillance and comparative effectiveness research in this area.…”
Section: Discussionsupporting
confidence: 56%
“…However, this piecemeal approach to data collection and the limitations of passive adverse event reporting in particular can lead to gaps in the availability of data and inconsistent analysis of data that are available. Hauser and colleagues simulated a prospective postmarket evaluation of the Sprint Fidelis ICD lead using a three-center database, finding that such active investigation may have raised red flags about early lead failure two years before Fidelis was actually taken off the market [34]. In the case of the recalled Riata ICD lead, the FDA did not mandate a postmarket study until after the lead was recalled in 2011 [33•].…”
Section: The Pma Pathway In Practicementioning
confidence: 99%
“…We have previously validated an active clinical-data-surveillance system, denoted DELTA (Data Extraction and Longitudinal Trend Analysis), capable of prospectively monitoring clinical registries and other detailed clinical data sources for safety signals 13,15,1822 . DELTA is a collection of integrated software components linking open-source database management and statistical analysis tools, and is designed to simultaneously support multiple risk-adjusted prospective safety-surveillance analyses of complex clinical datasets 13,15 ‎(See Supplementary Appendix for additional information regarding DELTA).…”
Section: Methodsmentioning
confidence: 99%